Review of in-space plasma diagnostics for studying the Earth's ionosphere. (30th June 2022) - Velásquez-García, Luis Fernando; Izquierdo-Reyes, Javier; Kim, Hyeonseok
Abstract: This review details the state of the art in in-space plasma diagnostics for characterizing the Earth's ionosphere. The review provides a historical perspective, focusing on the last 20 years and on eight of the most commonly used plasma sensors—most of them for in situ probing, many of them with completed/in-progress space missions: (a) Langmuir probes, (b) retarding potential analysers, (c) ion drift meters, (d) Faraday cups, (e) integrated miniaturized electrostatic analysers, (f) multipole resonance probes, (g) Fourier transform infrared spectrometers, and (h) ultraviolet absorption spectrometers. For each sensor, the review covers (a) a succinct description of its principle of operation, (b) highlights of the reported hardware flown/planned to fly in a satellite or that could be put in a CubeSat given that is miniaturized, and (c) a brief description of the space missions that have utilized such sensor and their findings. Finally, the review suggests tentative directions for future research.